2023
DOI: 10.1001/jamanetworkopen.2023.28798
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Factors in the Association of Shift Work and Depression and Anxiety

Abstract: IMPORTANCEShift work may lead to adverse health outcomes. Whether shift work is associated with depression and anxiety, and to what extent lifestyle mediates the associations, remains unknown.OBJECTIVETo explore the associations of shift work, its type, frequency, and working years with anxiety and depression and to examine the potential mediating role of lifestyles.Design, Setting, and ParticipantsThis cohort study included 175 543 employed or self-employed workers who participated in the UK Biobank baseline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Our results suggested that shift work participation, even with low frequency, may be associated with higher ORs of poor health outcomes. Previous studies have also found that shift work increased the risk of anxiety, depression, and coronary heart disease, neglecting shift frequency [5,54]. However, some studies have found that poor health outcomes increased following more frequent shift work [53].…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that shift work participation, even with low frequency, may be associated with higher ORs of poor health outcomes. Previous studies have also found that shift work increased the risk of anxiety, depression, and coronary heart disease, neglecting shift frequency [5,54]. However, some studies have found that poor health outcomes increased following more frequent shift work [53].…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-four studies included participants of both sexes. The number of participants in each study ranged from 11 (Wehrens et al, 2012) to 27 637 (Xu et al, 2023) in the shift work groups and from 14 (Geliebter et al, 2000;Wehrens et al, 2012;Yoshizaki et al, 2013) to 197 597 (Ho et al, 2022) Female and man participants ranged from 24.4 ± 2.9 years (Morikawa et al, 2008) to 56.3 ± 8.5 years (Lavie & Lavie, 2007) in the shift group and from 25.2 ± 2.9 years to 55.5 ± 3.6 years (Kubo et al, 2011). The mean period of exposure to shift work ranged from 2.1 ± 2.2 (Morikawa et al, 2008) to 28.6 ± 4.2 years (Dong et al, 2022).…”
Section: Population and Study Characteristicsmentioning
confidence: 99%
“…Despite substantial work examining the negative effects of stress on health, we currently lack an organized understanding of how stress leads to poor health and functioning in HCWs [ 31 ]. In this review, therefore, we apply the Job Demands-Resources (JD-R) health model [ 32 ], combining its core concept with a psychoneuroimmunological approach to elucidate neuroendocrine and neuroimmune mechanisms through which occupational stress may impact inflammation and immune dysregulation, resulting in long-lasting health consequences for HCWs.…”
Section: Introductionmentioning
confidence: 99%